Assessing the effects of immigrant status on placement in juvenile detention - Buckner, Zachary (Journal of crime and justice, 2023)
The United States hosts more immigrants than any country in the world and has been referred to as a nation of immigrants. While there has been a persistent focus on immigration in America, the focal point has typically been on the criminality of those who have migrated to the US. Overtime, negative rhetoric in the media and politics has stereotyped immigrants as criminals. Despite these negative perceptions, there is a dearth of literature on how immigrants are processed in the criminal justice system. Most research thus far assessing this relationship is limited to adult defendants, while paying little to no attention to how immigration status impacts juvenile justice outcomes. To add to the limited body of knowledge on immigrant status and court processing, this study uses a limited sample of adjudicated youth from the Pathways to Desistance study (N = 414) to explore how immigration status impacts dispositional outcomes in juvenile court. In comparison to non-immigrant youth, we find that first-generation immigrant status is positively associated with receiving an incarcerative sanction (i.e., detention). However, no significant effects were observed for second-generation immigrants. Implications for policy and practice are discussed.